2020
DOI: 10.3390/nu13010014
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Crossover Intervention Study on the Effect a Standardized Maté Extract (Ilex paraguariensis A. St.-Hil.) in Men Predisposed to Cardiovascular Risk

Abstract: (1) Background: Due to its richness in chlorogenic acids (CGAs), Maté (Ilex paraguariensis A. St.-Hil.) could be of interest in the prevention of cardiometabolic diseases, however clinical evidence are lacking. This trial aimed to evaluate the impact of maté CGAs, consumed in a daily dose achievable through traditional maté beverages, on parameters related to cardiometabolic risk. (2) Design: Thirty-four male volunteers aged 45–65 years and with at most one criteria of metabolic syndrome, were recruited for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…), rooibos (Aspalathus linearis), and yerba mate (Ilex paraguariensis) are important examples of herbal plants ( Figure 3 ) that are mostly found in African and South American local markets and have been traditionally used in the production of flavorful non-alcoholic beverages [ 88 , 89 , 90 ]. These plants have been demonstrated to have important health effects, such as as anti-cancer (in vitro) [ 91 ], anti-diabetes (in vivo) [ 92 ], or anti-inflammatory (in vivo) [ 93 ] effects. These health benefits play a role as commercial boosters for increasing market demand for new plant-based products with functional properties.…”
Section: Hibiscus Rooibos Yerba Mate As Sources Of Natural Bioactive ...mentioning
confidence: 99%
“…), rooibos (Aspalathus linearis), and yerba mate (Ilex paraguariensis) are important examples of herbal plants ( Figure 3 ) that are mostly found in African and South American local markets and have been traditionally used in the production of flavorful non-alcoholic beverages [ 88 , 89 , 90 ]. These plants have been demonstrated to have important health effects, such as as anti-cancer (in vitro) [ 91 ], anti-diabetes (in vivo) [ 92 ], or anti-inflammatory (in vivo) [ 93 ] effects. These health benefits play a role as commercial boosters for increasing market demand for new plant-based products with functional properties.…”
Section: Hibiscus Rooibos Yerba Mate As Sources Of Natural Bioactive ...mentioning
confidence: 99%
“…[ 28 ] A recent study showing a role of YM in the prevention of cardiometabolic disease in human patients, used 2250 mg of instant mate per day, divided in three doses. [ 29 ] In the present experiments a single daily dose was given, early in the morning, to avoid handling stress. For the same reason, 100 µL micropipettes were used.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, when mice received YM before exposure to sodium iodate, products of NRF2 and some of its target genes, such as SOD2, were available before oxidative stress. Priming effects could be essential for protection, as has been suggested for osteoblastic maintenance, [38] cardiometabolic disease, [29] and hepatic damage in overweight rats. [39] By contrast, NRF2 upregulation in the presence of cell damage might potentiate antisurvival effects of P53.…”
Section: Main Findingsmentioning
confidence: 99%
“…From these studies, a chronic intake of yerba mate has been shown to improve microcirculation in volunteers with high blood viscosity (13) , to decrease mass and percentage of body fat in obese subjects (14) or to increase the antioxidant capacity in overweight and dyslipidaemic subjects through the elevation of serum levels of paraoxonase-1 (15) . In men at moderate cardiovascular risk, the sub-chronic consumption of a standardised mate extract tended to improve some cardiometabolic biomarkers such as fasting glucose, HDLcholesterol or inflammatory markers but significance was not reached (5) .…”
mentioning
confidence: 91%
“…In this respect, the particularity of mate is to be, with coffee, a food source very rich in a diversity of chlorogenic acids which can constitute major contributors to the daily polyphenol intake in heavy consumers (4) . The composition in chlorogenic acids in mate differentiate from that of coffee by the presence of dicaffeoyl quinic acids that may represent up to half of total chlorogenic acids (5) . In addition to mono chlorogenic acids and dicaffeoyl quinic acids that both represent more than 90 % of total polyphenols, mate also contains some flavonol glycosides (3) .…”
mentioning
confidence: 99%